2022
DOI: 10.3390/en15228757
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparameter Tuning of OC-SVM for Industrial Gas Turbine Anomaly Detection

Abstract: Gas turbine failure diagnosis is performed in this work based on seven types of tag data consisting of a total of 7976 data. The data consist of about 7000 normal data and less than 500 abnormal data. While normal data are easy to extract, failure data are difficult to extract. So, this study mainly is composed of normal data and a one-class support vector machine (OC-SVM) is used here, which has an advantage in classification accuracy performance. To advance the classification performance, four hyperparameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…As a method that is easy to implement in Python using the scikit-learn package, we decided to implement OCSVM. It was presented in the article [71] that, using hyperparameters tuning (manual search, grid search, random search, and Bayesian optimization), the quality of the algorithm could be improved. The worst F1 score equal to 0.55521 was obtained by manual search, and the best F1 equal to 0.6488 was obtained for Bayesian optimization hyperparameter tuning.…”
Section: Algorithmsmentioning
confidence: 99%
“…As a method that is easy to implement in Python using the scikit-learn package, we decided to implement OCSVM. It was presented in the article [71] that, using hyperparameters tuning (manual search, grid search, random search, and Bayesian optimization), the quality of the algorithm could be improved. The worst F1 score equal to 0.55521 was obtained by manual search, and the best F1 equal to 0.6488 was obtained for Bayesian optimization hyperparameter tuning.…”
Section: Algorithmsmentioning
confidence: 99%
“…The Randomized Search is a non-exhaustive technique hence reducing the chance of overfitting of the model but may not guarantee an optimal combination of hyperparameters. Furthermore, it is observed that the randomized tunned models are more accurate than conventionally tunned models for the models having a less number of critical hyperparameters (Kang et al, 2022;Valarmathi & Sheela, 2021)- (Bischl et al, 2023). Therefore, authors used hyperparameter tunning technique and pseudo code are representing this optimization process are as follows:…”
Section: Randomized Searchcv Techniquementioning
confidence: 99%
“…The Randomized Search is a non‐exhaustive technique hence reducing the chance of overfitting of the model but may not guarantee an optimal combination of hyperparameters. Furthermore, it is observed that the randomized tunned models are more accurate than conventionally tunned models for the models having a less number of critical hyperparameters (Kang et al, 2022; Valarmathi & Sheela, 2021)–(Bischl et al, 2023). Therefore, authors used hyperparameter tunning technique and pseudo code are representing this optimization process are as follows: Initialize an empty dictionary variable “space”. Define a search function to save all hyperparameter subspaces. For each hyperparameter subspace stored in space, create a machine‐learning model with a set of hyperparameters obtained by random sampling. Fit each model by using training data samples. A dictionary score to store each model's accuracy or other performance metrics. Return the best model score and its parameters. …”
Section: Computational Intelligence Techniquesmentioning
confidence: 99%
“…Data-mining techniques have been widely employed across a range of domains to extract relevant knowledge from large datasets, in order to support informed decision-making processes [6]. In particular, increasing attention has been directed towards the application of data-mining techniques for knowledge extraction from time series data-i.e., an ordered set of observations recorded over time pertaining to a particular phenomenon and measured across a defined time span [7,8].…”
Section: Introductionmentioning
confidence: 99%